Anatomy assignment for Year 1 Block 4 - Mohd Radzuan, Hazulin (2021)
This assignment was given to the Year 1 Block 4 2019 / 2020 students as a requirement for their continuous assessment during the emergency remote teaching and learning period (ERTL).